The Cellular Protein P58(IPK) Regulates Influenza Virus mRNA Translation and Replication through a PKR-Mediated Mechanism - Goodman, Alan G. (American Society for Microbiology, 2007)
We previously hypothesized that efficient translation of influenza virus mRNA requires the recruitment of P58(IPK), the cellular inhibitor of PKR, an interferon-induced kinase that targets the eukaryotic translation initiation factor eIF2α. P58(IPK) also inhibits PERK, an eIF2α kinase that is localized in the endoplasmic reticulum (ER) and induced during ER stress. The ability of P58(IPK) to interact with and inhibit multiple eIF2α kinases suggests it is a critical regulator of both cellular and viral mRNA translation. In this study, we sought to definitively define the role of P58(IPK) during viral infection of mammalian cells. Using mouse embryo fibroblasts from P58(IPK−/−) mice, we demonstrated that the absence of P58(IPK) led to an increase in eIF2α phosphorylation and decreased influenza virus mRNA translation. The absence of P58(IPK) also resulted in decreased vesicular stomatitis virus replication but enhanced reovirus yields. In cells lacking the P58(IPK) target, PKR, the trends were reversed—eIF2α phosphorylation was decreased, and influenza virus mRNA translation was increased. Although P58(IPK) also inhibits PERK, the presence or absence of this kinase had little effect on influenza virus mRNA translation, despite reduced levels of eIF2α phosphorylation in cells lacking PERK. Finally, we showed that influenza virus protein synthesis and viral mRNA levels decrease in cells that express a constitutively active, nonphosphorylatable eIF2α. Taken together, our results support a model in which P58(IPK) regulates influenza virus mRNA translation and infection through a PKR-mediated mechanism which is independent of PERK.